Strategi Guru Pendidikan Agama Islam dalam Menerapkan Kurikulum Merdeka Belajar di SMA Negeri 1 Bangunrejo - Novtariska Dwi Miranti (Al-Bustan: Jurnal Pendidikan Islam, 2024)
This research is motivated by the implementation of the Merdeka Curriculum, which is a new curriculum introduced by the Ministry of Education and Culture of Indonesia as part of efforts to recover the education system post-pandemic. The Merdeka Curriculum offers a more flexible approach to learning, providing freedom in managing the learning process to make it more comfortable, active, and enjoyable. In this context, Islamic Education, which previously tended to use lecture methods, now emphasizes student activity and provides broader access to various sources for learning materials. The research findings indicate that Islamic Education teachers have made various efforts to implement the Merdeka Curriculum. These efforts include building student activity through triggering questions and collaborative learning, creating teaching modules to facilitate the teaching and learning process, and implementing the Pancasila student profile. However, challenges faced include disparities between teaching materials, student abilities, and time allocation.